Structure, development, and functional morphology of the cement gland of the giant danio, Devario malabaricus. Issue 11 (30th July 2019) - Nelson, Hannah M.; Coffing, Gabrielle C.; Chilson, Sarah; Hester, Kamil; Carrillo, Casandra; Ostreicher, Samantha; Tomamichel, Wendy; Hanlon, Samuel; Burns, Alan R.; Lafontant, Pascal J.
Abstract: Background: Aquatic species in several clades possess cement glands producing adhesive secretions of various strengths. In vertebrates, transient adhesive organs have been extensively studied in Xenopus laevis, other anurans, and in several fish species. However, the development of these structures is not fully understood. Results: Here, we report on the development and functional morphology of the adhesive gland of a giant danio species, Devario malabaricus . We found that the gland is localized on the larval head, is composed of goblet‐like secretory cells framed by basal, bordering, and intercalated apical epithelial cells, and is innervated by the trigeminal ganglion. The gland allows nonswimming larvae to adhere to various substrates. Its secretory cells differentiate by 12 hours postfertilization and begin to disappear in the second week of life. Exogenous retinoic acid disrupts the gland's patterning. More importantly, the single mature gland emerges from fusion of two differentiated secretory cells fields; this fusion is dependent on nonmuscle myosin II function. Conclusions: Taken together, our studies provide the first documentation of the embryonic development, structure, and function of the adhesive apparatus of a danioninae . To our knowledge, this is also the first report of a cement gland arising from convergence of two bilateral fields. Key Findings: The giant danio ( Devario malabaricus ) possesses a functional cement gland. Developmental and functional morphology of the cement gland. First evidence of a single mature cement gland emerging from the convergence and fusion of two differentiated secretory cells fields. Cement gland field fusion requires non-muscle myosin II function.